Safety, pharmacokinetics and pharmacodynamics of AMG 811, an anti-interferon-γ monoclonal antibody, in SLE subjects without or with lupus nephritis. Issue 1 (14th September 2017) - Boedigheimer, Michael J; Martin, David A; Amoura, Zahir; Sánchez-Guerrero, Jorge; Romero-Diaz, Juanita; Kivitz, Alan; Aranow, Cynthia; Chan, Tak Mao; Chong, Yip Boon; Chiu, Kit; Wang, Christine; Sohn, Winnie; et al.
Abstract : Objective: To evaluate safety, pharmacokinetics and pharmacodynamics of anti-interferon (IFN)-γ monoclonal antibody AMG 811 in subjects with SLE without or with lupus nephritis (LN). Methods: In this phase Ib, randomised, multiple-dose escalation study (NCT00818948 ), subjects without LN were randomised to subcutaneous AMG 811 (6, 20 or 60 mg) or placebo and subjects with LN were randomised to subcutaneous AMG 811 (20, 60 or 120 mg) or placebo every four weeks for three total doses. Outcomes included incidence of adverse events (AEs); pharmacokinetics; levels of serum proteins (CXCL-10, interleukin 18, monocyte chemotactic protein-1); changes in gene transcript profiles and clinical parameters (Safety of Estrogen in Lupus Erythematosus National Assessment-Systemic Lupus Erythematosus Disease Activity Index (SELENA-SLEDAI) scores, proteinuria, anti-double-stranded DNA (anti-dsDNA) antibodies, C3 complement, C4 complement). Results: Fifty-six subjects enrolled (28 SLE without LN; 28 with LN). Baseline mean SELENA-SLEDAI scores were 2.2 and 12.0 for SLE subjects without and with LN, respectively. Most subjects reported an AE; no meaningful imbalances were observed between AMG 811 and placebo. Pharmacokinetic profiles were similar and mostly dose-proportional in subjects without or with LN. AMG 811 treatment reduced CXCL-10 protein levels and blood-based RNA IFN-γ Blockade Signature compared with placebo. Reductions were less pronounced and not sustained in subjects with LN, even at the highest dose tested, compared with subjects without LN. No effect on SELENA-SLEDAI scores, proteinuria, C3 or C4 complement levels, or anti-dsDNA antibodies was observed. Conclusion: AMG 811 demonstrated favourable pharmacokinetics and acceptable safety profile but no evidence of clinical impact. IFN-γ-associated biomarkers decreased with AMG 811; effects were less pronounced and not sustained in LN subjects. Trial registration number: NCT00818948; results.